Analysis of Extreme Precipitation Events in Ganjiang River Basin Since the Second Half of the 20th Century - ZOU Xiongyuan; LIU Yanping; WAN Dan; WU Xia; ZHENG Kang; ZHAO Junkai (Renmin Zhujiang)
Under the background of global warming,the frequency of local extreme precipitation events increases gradually.This paper selects six extreme precipitation indexes such the extreme precipitation threshold (EPT),extreme precipitation (R95),extreme precipitation days (RD95),extreme precipitation intensity (RI95),maximum precipitation for five consecutive days (RX5day) and maximum precipitation for one day (RX1day),and analyzes the extreme precipitation events in Ganjiang River Basin from 1964 to 2013 by percentile threshold method,M-K trend analysis method,sliding t test method and Kriging spatial interpolation method.The results show that:①The extreme precipitation index of most stations in Ganjiang River Basin shows non-significant upward trend;②The mutation time of extreme precipitation index of each station is mostly concentrated in the 1980s and 1990s,and a few stations have significant mutation (α=0.01);③Except for RD95,all the extreme precipitation indexes decrease from east to west,on the contrary,RD95 decreases from west to east.The research results can provide reference for flood control,disaster reduction and water resources development and utilization in Ganjiang River Basin.